Ghosting about : exegesis for MFA at Massey University - Steelsmith, Mark Antony (Massey University, 2017)
There are more things I have forgotten than I care to remember, yet, I go looking for them. My work uses light, sound, cardboard boxes and ghosts to help me remember. It is an exploration of memory and daydreaming whilst wandering around the urban-scape of Wellington. Memory has a disruptive influence on the architecture and spaces we occupy. Using Mark Fisher’s lost futures version of Hauntology I investigate how my memories have been tied up in a particular part of the city. I use ghosting as my framework to look through windows, peer into the past and imagine the future that never was. My mobile phone has become a note taking device as I go “ghosting those same streets”.
Keywords: Mark Antony Steelsmith; Criticism and interpretation; Autobiographical memory in art; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art